Albumin versus solvent/detergent–treated pooled plasma as replacement fluid for long‐term plasma exchange therapy in a patient with primary hypertriglyceridemia and recurrent hyperlipidemic pancreatitis. Issue 3 (4th November 2015) - Di Bona, Danilo; Cefalù, Angelo B.; Scirè, Elisabetta; Lima, Giacomo M.; Rizzo, Claudia Maria; Giammanco, Antonina; Barbagallo, Carlo M.; Averna, Maurizio R.; Rizzo, Sergio; Caruso, Calogero
Abstract : BACKGROUND: Chylomicronemia syndrome is a metabolic condition characterized by severe fasting hypertrigliceridemia (≥1000 mg/dL) and other clinical features including chronic abdominal pain and recurrent acute pancreatitis. In patients with acute or recurrent pancreatitis, plasma exchange (PEx) is indicated for the treatment of acute disease and prevention of recurrence. The use of plasma instead of albumin as replacement fluid has been suggested for its putative ability to replace the deficient enzyme possibly leading to better clinical improvement. CASE REPORT: A 40‐year‐old man with chylomicronemia syndrome due to a newly identified loss‐of‐function mutation in the lipoprotein lipase (LPL) gene (IVS2, c.250‐1G/C) has been treated at our hospital since the age of 13. From age 18 to age 34, the patient had five episodes of acute pancreatitis while his triglyceride (TG) levels were extremely high (2500–4000 mg/dL). As the TG levels remained stable over 4000 mg/dL despite the maximum medical treatment, the patient started long‐term PEx treatment on a weekly basIs. Both albumin and plasma have been used as replacement solution. Thirty months from the beginning of this treatment, no episode of acute pancreatitis has been reported, and the chronic abdominal pain fully disappeared. No differences were observed between the use of albumin or plasma as replacement solution. CONCLUSION: Long‐term PEx is effective in preventing the recurrence of acute pancreatitis and in treatment of chronic abdominal pain in this patient with chylomicronemia syndrome. Plasma is not more effective than albumin in lipid reduction, likely because of its extremely low enzyme content. Therefore, in patients with LPL deficiency serum albumin should be preferred to plasma as replacement fluid because of the low rate of side effects and reduced costs.